Supplier selection for competitive advantage in supply chain: an integrated fuzzy analytic hierarchy process using simulation approach. (2015) - Dewangan, Devendra Kumar; Agrawal, Rajat; Sharma, Vinay
In today's global competitive scenario, supplier selection in the supply chain is very crucial for a competitive advantage in the manufacturing sector in India. The study presents an integrated approach for selection of the appropriate supplier to addressing the issues like innovation, after sale services and pricing. The paper proposed to solve the fuzzy analytic hierarchy process (FAHP) problem that combines the fuzzy preference programming (FPP) method to derive a crisp priority vector straightforward way from a set of fuzzy judgments by using simulation. This paper focused on the real situation, to demonstrate the effectiveness of the proposed model. The effectiveness of the model is discussed through a case conducted for Indian-based electrical manufacturing (ABC) company. For the preparation of their products, the company procures raw materials from different suppliers. Merely, a question arises which supplier is the best for the company.